ETD 2003 - Sixth International Symposium on Electronic Theses and Dissertations - Filipi Matutinović, Stela (Infotheca - Journal for Digital Humanities, 2024)
The symposium held in Berlin from 20-24.05.2003 was the sixth annual conference organized by the "Networked Digital Library of Theses and Dissertations" (NDLTD), with the title "Next steps - Electronic Theses and Dissertations Worldwide".